Good Habits: Textile Work and the Creation of Monastic Identities at the Convent of Kirkjubæjarklaustur - Parsons, Emily Mary, 1994- (2018)
The secular household production of textiles was one of the major economic activities of medieval Iceland, with current archaeological and historical studies focusing on the commercial and social function of cloth. However, archaeological excavation at the convent of Kirkjubæjarklaustur reveals that textile objects comprise a significant portion of the material culture of the religious site, and thus likely had a prominent role in the activities of monastic women. This role remains understudied in medieval devotion studies, and I argue that the textile production activities were significant in constituting both personal, intimate religious practices, and communal devotions. This thesis examines the surviving textile material and objects related to textile production from Kirkjubæjarklaustur, to understand the significance of textile production in women's religious lives. What did it mean for the nuns, to create cloth in the convent environment? How did the materials produced engage with monastic religious practices, and how were these concepts gendered? In what ways can the actions and meanings imbued in the surviving material objects be interpreted regarding monastic identities? And, what strategies were employed by the nuns at Kirkjubæjarklaustur to situate themselves within the monastic system? I examine the way objects like textiles and textile tools become entangled and active agents in the construction and performance of identity for female monastics. By drawing on frameworks such as performativity, habitus, and ritual communication, the material objects such as looms, knitting needles, and religious textiles like altar cloths are understood both in regard to their stylistic and technological features, as well as their symbolic and social meaning. To contextualize these objects within existing dialogic practices, I discuss the social conventions around female piety, particularly the emphasis on female saints lives and Marian cult practices through material excavated at Kirkjubæjarklaustur and the ...